The Prevalence and Overlap of Interstitial Cystitis/Bladder Pain Syndrome and Chronic Prostatitis/Chronic Pelvic Pain Syndrome in Men: Results of the RAND Interstitial Cystitis Epidemiology Male Study - Suskind, Anne M; Berry, Sandra H; Ewing, Brett A; Elliott, Marc N; Suttorp, Marika J; Clemens, J. Quentin (The Journal of urology, 2013)
Purpose As part of the RICE (RAND Interstitial Cystitis Epidemiology) study, we developed validated case definitions to identify interstitial cystitis/bladder pain syndrome in women and chronic prostatitis/chronic pelvic pain syndrome in men. Using population based screening methods, we applied these case definitions to determine the prevalence of these conditions in men. Materials and Methods A total of 6,072 households were contacted by telephone to screen for men who had symptoms of interstitial cystitis/bladder pain syndrome or chronic prostatitis/chronic pelvic pain syndrome. An initial 296 men screened positive, of whom 149 met the inclusionary criteria and completed the telephone interview. For interstitial cystitis/bladder pain syndrome 2 case definitions were applied (1 with high sensitivity and 1 with high specificity), while for chronic prostatitis/chronic pelvic pain syndrome a single case definition (with high sensitivity and specificity) was used. These case definitions were used to classify subjects into groups based on diagnosis. Results The interstitial cystitis/bladder pain syndrome weighted prevalence estimates for the high sensitivity and high specificity definitions were 4.2% (3.1–5.3) and 1.9% (1.1–2.7), respectively. The chronic prostatitis/chronic pelvic pain syndrome weighted prevalence estimate was 1.8% (0.9–2.7). These values equate to 1,986,972 (95% CI 966,042–2,996,924) men with chronic prostatitis/chronic pelvic pain syndrome and 2,107,727 (95% CI 1,240,485–2,974,969) men with the high specificity definition of interstitial cystitis/bladder pain syndrome in the United States. The overlap between men who met the high specificity interstitial cystitis/bladder pain syndrome case definition or the chronic prostatitis/chronic pelvic pain syndrome case definition was 17%. Conclusions Symptoms of interstitial cystitis/bladder pain syndrome and chronic prostatitis/chronic pelvic pain syndrome are widespread among men in the United States. The prevalence of interstitial cystitis/bladder pain syndrome symptoms in men approaches that in women, suggesting that this condition may be underdiagnosed in the male population.